Degradation of imazapic and imazapyr herbicides in the presence of optimized oil palm empty fruit bunch and rice husk biochars in soil - Yavari, S. (2019)
Imidazolinones as a persistent and active herbicides group have potential risks to non-target organisms in the environment. Biochar is a carbon-rich sorbent used as an amendment to change soil properties and its microbial communities effective on pesticides degradation rate. The present study was the first to compare empty fruit bunch (EFB) of oil palm and rice husk (RH) biomasses as biochar feedstock for remediation of imidazolinones-contaminated soils. Degradations of imazapic, imazapyr, and a mixture of them (OndutyÂ®) was investigated in the presence of the optimized biochars in the soil during a 70-days incubation. Based on the results, the polar herbicides were resistant to hydrolysis degradation. Photolysis rates of the herbicides reduced significantly in the presence of the biochars in the soil. EFB biochar had greater effects due to its chemical compositions and surface functional groups. Photo-degradation of imazapyr was more affected by biochars amendment. The imidazolinones bio-degradation, however, accelerated significantly with the presence of EFB and RH biochars in soil with the greater effects of RH biochar. It was concluded that the application of the optimized EFB and RH biochars as an innovative sustainable strategy has the potential to decrease the persistence of the imidazolinones and minimize their environmental hazards. Â© 2018